Microbial burden of Coliform bacteria in commercially available Poultry-feeds (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Microbial burden is a great threat in production, transportation and distribution of poultry feed. E. coli and Salmonella is an important cause of food borne disease in humans throughout the world and is a significant cause of morbidity, mortality and economic loss. Therefore, the present study was designed to isolation of common coliform bacteria from the Poultry feed.Material and Methods: This study was performed as per the standard protocol of microbial analysis of poultry feed to isolate and identify the common pathogen E. coli and Salmonella present in feed sample.Results: Out of 70 samples examined, 62(88.57%) showed growth in which E.coli was 38(61%) and 24(39%) was Salmonella and 16(22.86%) samples showed fair growth and 8(11.42%) samples showed no growth.Conclusion:  Most of the poultry feed sample of this area was found to be highly contaminated with E. coli and Salmonella.